Arg–Tyr cation–π interactions drive phase separation and β-sheet assembly in native spider dragline silk - Hannah R. Johnson; Kevin Chalek; Nesreen Elathram; Andy T. Chau; Anikin Rae Domingo; Julian E. Aldana; Hieu Nguyen; Alexia de Loera; Brianna A. Duarte; Lado Shapakidze; David Onofrei; Galia T. Debelouchina; et al. (Proceedings of the National Academy of Sciences, 2025)
Liquid–liquid phase separation (LLPS) is a fundamental principle of protein organization in intrinsically disordered proteins (IDPs) and biomaterials, yet the residue-level interactions that link condensation to structural ordering remain poorly defined. In spider dragline silk, LLPS is believed to initiate the transition from soluble spidroin dope into β-sheet–rich fibers that provide exceptional toughness, yet how sequence-specific motifs govern this process has been unclear. Here, we combine isotope-edited solution NMR, dynamic nuclear polarization (DNP)–enhanced solid-state NMR, molecular dynamics simulations, and AlphaFold3 modeling to define the molecular role of arginine and tyrosine in Latrodectus hesperus dragline silk. Phosphate triggers LLPS while preserving intrinsic disorder, with arginine exhibiting the largest chemical shift perturbations. Simulations reveal that phosphate displaces hydration water to promote Arg–Tyr cation–π interactions and weaken Arg–poly(Ala) contacts. Solid-state NMR directly detects Arg–Tyr contacts in spun fibers, demonstrating that arginine is partially incorporated into β-sheet interfaces while tyrosine frequently adopts β-turn conformations. AlphaFold3 models corroborate these interfacial geometries and reproduce experimental chemical shifts, supporting persistent Arg–Tyr interactions at structured–unstructured boundaries. Together, these results identify Arg–Tyr contacts as critical “sticker” interactions that mediate condensation, nucleate local order, and stabilize fiber architecture. More broadly, this work establishes a mechanistic link between residue-specific chemistry, LLPS, and hierarchical assembly in a structural protein. These insights highlight how weak multivalent interactions bridge disordered and ordered states, providing a general framework for condensate-driven assembly in biology and guiding biomimetic material design.